Comparison of emergency medical residency pre-board and board exams among universities of medical sciences in Iran - Mohammad Barzegar; Reza Ghaffari; Farzad Rahmani; Amir Ghaffarzad; Hamid Soltani Zangbar; Solmaz Fallahi; Amir Hossein Jafari-Rouhi (Tabriz University of Medical Sciences, 2020)
Background: Designing and conducting residency exams have been the province of type I universities since 2005, based on the plans of the Medical Education Council. This study compared emergency medical residency pre-board and board exam results among the universities of medical sciences in Iran. Methods: This cross-sectional descriptive study consisted of 600 questions from residency preboard exams and 150 questions from board exams in 2013-2014, as well as 600 questions from residency promotion exams and 150 questions from the board exam in 2013-2014 and 2014- 2015 at the Tabriz, Shahid Beheshti, Mashhad, and Tehran Universities of Medical Sciences. All questions were at the level I through III by Bloom's taxonomy. Structural principles were evaluated using Millman's checklist. All data were analyzed using SPSS 18 with chi-square tests. Results: The mean percent of more contextualized questions of the questions at Bloom's taxonomy levels II and III in residency pre-board exam questions was 76.6% in 2013-2014 and 86.6% in 2014-2015 among the four universities. In terms of structural principles, the percentage of board exam questions that aligned with Millman's structural principles was 100.0% and 99.3% in 2013-2014 and 2014-2015, respectively. For the residency pre-board exam in 2014- 2015, the mean discrimination index was 0.14 (low), and the mean of the difficulty factor was 0.64 (appropriate). Conclusion: Questions at Bloom's taxonomy levels II and III were higher in 2014-2015 in comparison to those in 2013-2014, and the percentage of the correctly-structured questions was high and did not significantly change from 2013-2014 in comparison to that of 2014-2015.